PBG 9. QTL Mapping for agronomic, yield, and biofortification traits in IR95040 x Jamir RILs population of Rice (Oryza sativa L.) (2018)
Iron (Fe) and Zinc (Zn) deficiencies are among the most prevalent micronutrient deficiencies worldwide primary affecting children, pregnant and lactating women in developing countries. In the Philippines, 30% of the population is zinc-deficient. Rice provides energy and nutrition to more than half of the world’s population but the commonly grown high-yielding rice varieties are a poor source of micronutrients especially in polished form. Rice biofortification is one of the most sustainable approaches to tackle micronutrient malnutrition. We conducted QTL mapping using 295 recombinant inbred lines (RILs) derived from IR95040 x JAMIR cross. RILs were phenotype for agronomic, yield, and Fe and Zn during 2017 dry season and 2017 wet season. RILs were genotyped using 7K SNP Chip. A linkage map consisting of 578 SNP markers was constructed and QTL analysis was carried out using Inclusive Composite Interval Mapping implemented in QTL IciMapping v4.1 software. We detected a total of 27 QTLs for the ten traits that explain 7.0% - 37.1% of the phenotypic variance. The QTL for grain yield was contributed by IR95040 while all QTLs for plant height, number of tillers, and number of panicles, grain width, and Zn were contributed by the high-Zn parent JAMIR. Two QTLs (qFe7 and qFe8) and three QTLs (qZn5, qZn6, and qZn7) were identified for Fe and Zn, respectively. The consistent large-effect QTL for Zn on chromosome 5 have additive effects of 3.0 ppm and 1.9 ppm during 2017 DS and 2017 WS, respectively. Furthermore, we identified OsZIP5 and OsZIP9 as candidate genes for Zn on chromosome 5 and OsNaS3 for grain Fe and Zn on Chromosome 7 which are involved in metal transport. These QTLs and candidate genes help to further elucidate the genetic basis of grain Fe and Zn concentration, and may prove useful for future MAS breeding for these important traits.